Aspects of the community structure and reproductive ecology of the common sea-urchin Parechinus angulosus Leske around the Cape Peninsula, South Africa - Fricke, Alexander Hermann (Department of Oceanography, 2023)
The geographic distributionof Parechinus angulosus according to present II records extend from Umhlali (Zululand) to Luderitz Bay (Day, 1974). The urchins are therefore adapted to a wide range of temperatures. Maximum fluctuations probably occur along the stretches of coastline affected by upwelling, the South-West, and west coasts, with differentials of twelve degrees Centigrade and more. Furthermore, these fluctuations may take place within a matter of a few hours or even less, i.e., almost capriciously Like temperature changes encountered on land but, unlike, the latter, by virtue of movement of different water masses, rather than cooling rate. The importance of temperature as a regulator of reproductive cycles in marine organisms, specifica'ly invertebrates, is discussed in Giese and Pearse's (1974) detailed review on the subject. A local study by Newman (1969) considers the effect of temperature on the spawning behaviour of abalone (Haliotis midae). This study was commenced in the light of this information and subjective preliminary observations underwater, which revealed striking density and relative size differences between urchins on the Atlantic side of the Peninsula and in the warmer False Bay. A detailed in situ record of sea temperatures at two study sites, Robben Island and Millers Point was obtained by installing temperature measuring devices. This monitoring covered a period of one year, while coupled with monthly collections of urchins in the mature size range. The variations of male and female gonad indices were found to be essentially in agreement, though lagging behind sea temperature changes. The spawning periods of urchins at both study sites was similar, occurring in spring and autumn, despite the significantly different water temperature averages. A clear pattern was observed at Millers Point, while being poorly defined at Robben Island. This is in agreement with the findings of Newman (1967, 1969), whose observations included data from St. Helena Bay to beyond Port Elizabeth. Newman found higher spawning intensities at localities having a clear seasonal pattern of sea temperature variations, compared to those of low seasonality, in other words, better synchrony of gamete release. A possible mechanism was mentioned by Giese & Pearse (1974), suggesting that the ripest individuals may be induced to spawn by a sharp temperature change, thereby stimulating other less mature individuals to follow suit. The degree of perturbation necessary to initiate such a sequence can vary widely. Many species are known to have breeding seasons in areas where temperature fluctuations are slight, such as parts of the polar, tropical, and abyssal ocean. My observations indicate that a confused temperature regime, involving rapid changes, such as occur during periodic upwelling cycles, results in repeated, incomplete spawn-outs. Consequently, gonad indices are always lower at Robben Island tha·n at Millers Point. Urchins at both localities show a low reproductive status during winter. Stained histological thin sections were prepared of gonad portions of selected urchins of both sexes covering all _maturity. (Gonad index) stages and compared with lipid values obtained for the same respective animals. It was found that during maturation, there is a gradual build-up of gametes passing through the well-known developmental stages, rather than a snap conversion of accumulated storage material (I only tested for lipid for practical reasons) into sperms or eggs. Even relatively regressed {low gonad index) urchins could be induced to release fertilizable spawn, by injection of potassium chloride solution. Lipid values form a surprisingly small portion of the total dry mass of the urchin, when it is realised that it is the gonads which function as the major storage organ in addition to the . intestine (Boolotian, 1966). Except for a few high, possibly spurious, values, male 1 ipid levels were on the whole lower than those found for females. It would have been interesting to have values for glycogen as well for comparison, particularly since calorific values obtained for representative male and female Parechinus by micro-bomb calorimetry were found to be in very close agreement, in fact practically identical. The significant mean size differences between urchins of the 2 study sites could be shown to be very 1 ikely due to the availability of food. This was shown by a comparison of gut states of urchins collected during the period of study. Although it is true that suspended food material is more plentiful in an upwelling locality, like Robben Island and unlike Millers Point, this situation is only important to the planktonic and recently settled juvenile stages of Parechinus. Once the animal has reached a test diameter of 10 mm (Greenwood, 1980), macroscopic and attached food sources A~~ required. In this respect Robben Island is clearly limiting. Hence urchins of a smaller mean size relative to Millers Point enter the reproductive life eyelet, since only that fractfon over and above the animal 1 s metabolic requirements is available for growth and reproduction. The significantly lower (one quarter) gamete output of urchins from Robben Island is evidence of this fact. Recruitment of Parechinus into the benthonic stage appears to be strongly dependent on substrate, in that the eroded, slaty structure of the reefs at Robben Island afford many suitable microhabitats to juveniles at this particularly vulnerable stage, while the rounded granite boulder terrain at Millers Point does not offer a comparable number and choice of such sites. Tegner and Dayton (1977) showed that substrate type may play an important role in the recruitmaitof a Californian species, Strongylocentrotus purpura~us, which like Parechinus is flexible in its recruitment behaviour, which means that the urchins select suitable sites from a range of choices, while - S. franciscanus juveniles shelter under the spine canopy of adults. The size class study sites must be seen in this light. In effect then we have a situation, where substrate type and availability jointly select against the smaller size classes at Millers Point. The strongly contagious distribution of Pa:l'echinus is very likely a response to the proximity of food. Since debris tends to accumulate on horizontal surfaces, urchins can be expected to be more numerous there than on inclined substrate. This was found to be true in a study by Vel imi rov et al. (1977), who made the dividing line between horizontal and vertical at 45° inclination. In addition, minor adjustments according to sea strate take place. It was found that under turbulent conditions urchins shelter on rockfaces away from I the sea and under overhangs to avoid strong swell action and contact with loose material such as torn off kelp plants. Predation was not studied and therefore only tentative impressions gained per chance in the field are at hand. Robbeneiland lying in a security area is largely undisturbed and harbours many rock lobsters (Jasus lalandii), which prey on Pa:l'echinus in addition to their main food, the ribbed mussel (Aulacomya ater). Indeed, lobsters were seen to feed on urchins on a number of occasions, apparentl_y selecting the smaller individuals. rare for many years through overexploitation. At Millers Point Jasus has been There appears to be no significant departure from the 1 :1 sex·ratio at either site according to Chi-square analysis. However, a more powerful analysis of variance and co-variance indicated a higher number of males at Robbeneiland. The discrepancy may be due to the fact that while Chi-square analysis was done on small (30 batches of urchins collected on a monthly basis and comprising mainly sexually matureindividuals at various stages of gonadal development, the Anova involved material obtained during seasonal transects including a wide range of size classes, particularly at Robbeneiland . Indeterminate urchins were excluded from the analysis, but nevertheless, misidentifications favouring males did occur. It would therefore appear that there is little reason to assume that the sex ratio of Parechinus is significantly unsymmetrical.